CTAB-assisted hydrothermal synthesis of tungsten oxide microflowers - Yayapao O. (2014)
Orthorhombic tungsten oxide (o-WO3) was synthesized by 200 °C, 24 h hydrothermal reactions of ammonium metatungstate hydrate solutions containing different volumes of 1 M HCl and cetyltrimethylammonium bromide (CTAB) cationic surfactant. The as-synthesized products were characterized by X-ray powder diffraction (XRD), Fourier transform infrared (FTIR) and Raman spectroscopy, and scanning and transmission electron microscopy (SEM, TEM), including UV-visible and photoluminescent (PL) spectroscopy. These analyses showed that their phases and morphologies were controlled by the acidity of the solutions. In 7.50 ml 1 M HCl-added solution, the product was o-WO3 microflowers, with microsquare layers growing out of their cores. FTIR and Raman vibrations of WO, O-W-O, and W-O-W stretching modes were detected, and showed typical crystalline WO3. Their optical properties showed a maximum absorption at 275 nm in the UV region and a maximum emission peak at 375 nm. The possible formation mechanism of o-WO3 microflowers was also proposed according the experimental results. © 2010 Elsevier B.V. All rights reserved.